2023
DOI: 10.1093/genetics/iyad218
|View full text |Cite
|
Sign up to set email alerts
|

The fitness consequences of genetic divergence between polymorphic gene arrangements

Brian Charlesworth

Abstract: Inversions restrict recombination when heterozygous with standard arrangements, but often have few noticeable phenotypic effects. Nevertheless, there are several examples of inversions that can be maintained polymorphic by strong selection under laboratory conditions. A long-standing model for the source of such selection is divergence between arrangements with respect to recessive or partially recessive deleterious mutations, resulting in a selective advantage to heterokaryotypic individuals over homokaryotyp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…It has also been suggested that load may promote polymorphism through associative overdominance, in which heterokaryotypes carrying different sets of deleterious recessive alleles have increased fitness relative to homokaryotypes due to masking of the deleterious recessives [23]. While examples of heterokaryotype advantage are known [24], it is difficult to prove that associative overdominance is the cause, especially given that the conditions under which it is likely to evolve are highly restrictive [25]. In D. chrysippus, there is no compelling evidence for heterozygote advantage: the three most common haplotype groups each occur in large regions of monomorphism, and broad clines suggest that polymorphism in the hybrid zone reflects a balance between selection (local adaptation) and extensive dispersal [37] rather than heterokaryotype advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that load may promote polymorphism through associative overdominance, in which heterokaryotypes carrying different sets of deleterious recessive alleles have increased fitness relative to homokaryotypes due to masking of the deleterious recessives [23]. While examples of heterokaryotype advantage are known [24], it is difficult to prove that associative overdominance is the cause, especially given that the conditions under which it is likely to evolve are highly restrictive [25]. In D. chrysippus, there is no compelling evidence for heterozygote advantage: the three most common haplotype groups each occur in large regions of monomorphism, and broad clines suggest that polymorphism in the hybrid zone reflects a balance between selection (local adaptation) and extensive dispersal [37] rather than heterokaryotype advantage.…”
Section: Discussionmentioning
confidence: 99%
“…The fitness consequences of a supergene could also change if selective pressures change over time or across space, potentially limiting the value of a supergene in a changing environment or during dispersal into a new environment [22]. Even in a stable environment, inversion supergenes may be subject to accumulation of increased mutational load compared to the rest of the genome due to their reduced opportunities for recombination and reduced effective population size (Ne) (due to the effective subdivision of the population in that part of the genome) [23][24][25]. Some theoretical models suggest that this may lead to heterokaryotype advantage through sheltering of recessive deleterious mutations (associative overdominance) [23][24][25], or failure of locally adapted inversions to reach high frequency [26].…”
Section: Introductionmentioning
confidence: 99%